Роль Т. Г. Шевченка у розвиткові українсько-польських літературних зв’язків першої половини XIX століття - Козаченко, О.М. (Культура народов Причерноморья, 2013)
Стаття присвячена українсько-польським літературним зв'язкам першої половини ХІХ
століття. Особливу увагу автор приділяє постаті Т.Шевченка, який багато в чому визначив характер
цих зв'язків. Статья посвящена характеристике украинско-польских литературных связях первой
половины ХІХ века. Особое внимание автор уделяет личности Т. Шевченко, который во многом
определил характер этих связей. An article deals with Ukrainian-Polish literature connections of the first half of XIX century. An
author points out on the personality of T.Shevchenko who, in many ways, defined the character of these
connections. Theme ukrainian-polish literary connections of this period most successfully and full, consider, it is
possible to expose through the prism of connections of Taras Shevchenko with the representatives of front-rank
Polish intelligentsia of the first half ХІХ a century. Already during studies in Academy of arts Shevchenko
intermingled with the Polish writers, with Polish revolutionary adjusted intelligentsia, among that his works
caused the real admiration and пошанування. Modern researchers of work of T.Shevchenko operates the
numerous testifying to the limits of acquaintance of Shevchenko with the Polish culture of his time, and by too
Polish literature of time of romanticism( by works of А.Міцкевича in particular). Two things indisputable :
distributions in the handwritten lists of works of Shevchenko among Polish public and deep awareness,
mastering the Ukrainian poet all considerable, that democratic Polish intelligentsia did for freedom and
development of culture. These were influences that left the track not only on ukrainian-polish literary-public
connections. Shevchenko takes into account the achievement of Polish romanticism in industry of subjects, range
of problems and poetics, but also does the new opening that Polish romantic literature did not know. The epoch
of nobiliary revolutionism came to an end, twenty-four hours began revolutionary-democratic, and Shevchenko
became her express and singer.